Unconventional Monetary Policy in a Financially Heterogeneous Monetary union - Benjamin Schwanebeck (Philipps-University Marburg, School of Business and Economics, 2017)
The cross-country interbank market in the euro area was a crucial transmission channel of financial stress. By using a two-country DSGE model of a financially heterogeneous monetary union where banks in one country lend funds to their foreign counterparts, I examine its role as shock ampli.er and the implications for unconventional policy interventions Using the international interbank market to pool and insure against shocks is not neutral, the resulting spillovers rather act as shock multipliers on union output. Country-specific unconventional policies of direct lending to firms seem to be the most effective interventions in terms of union and relative output stabilization. The higher the size of the interbank market, the more effective are these policies in terms of union stabilization. The effectiveness of interventions in the interbank market seems to be very sensitive to the type of shock and the interbank market size. Hence, the central bank should rather shy away from this policy as it is only useful under specific circumstances.
Keywords: E32; E44; E58; F45; 330; financial intermediation; financial frictions; interbank market; monetary union; unconventional policy